2015
DOI: 10.2355/isijinternational.isijint-2015-259
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Diffusivity in the Welding Zone of Two High Strength Experimental Microalloyed Steels

Abstract: Using permeation tests, determination of hydrogen trapping and microhardness measurements, the effect of the microstructure on the hydrogen diffusivity was analyzed in the welding zone of two highstrength experimental microalloyed steels called M1 steel, with a martensite and bainite microstructure and M2 steel with a quasi-polygonal ferrite (QPF), acicular ferrite (AF) and martensite-austenite (M/A) microstructure. Determination of the diffusivity was performed using electrochemical permeation tests, and hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In the present work, grain size of the ferrite sample with coarser microstructure did not reach this critical value, thus hydrogen diffusion coefficient was still growing in the order CP1000‐CPF‐CPF_CM. López‐Martínez et al also observed that larger grains and smaller grain boundary area led to fewer diffusion paths and as a result to lower diffusion coefficients in steel. On the other side, Stopher et al reported that the amount of trapping sites increased with decreasing grain size.…”
Section: Discussionmentioning
confidence: 97%
“…In the present work, grain size of the ferrite sample with coarser microstructure did not reach this critical value, thus hydrogen diffusion coefficient was still growing in the order CP1000‐CPF‐CPF_CM. López‐Martínez et al also observed that larger grains and smaller grain boundary area led to fewer diffusion paths and as a result to lower diffusion coefficients in steel. On the other side, Stopher et al reported that the amount of trapping sites increased with decreasing grain size.…”
Section: Discussionmentioning
confidence: 97%